Enhanced Vascularization in Hybrid PCL/Gelatin Fibrous Scaffolds with Sustained Release of VEGF - Wang, Kai (Biomed Res Int, 2015)
Creating a long-lasting and functional vasculature represents one of the most fundamental challenges in tissue engineering. VEGF has been widely accepted as a potent angiogenic factor involved in the early stages of blood vessel formation. In this study, fibrous scaffolds that consist of PCL and gelatin fibers were fabricated. The gelatin fibers were further functionalized by heparin immobilization, which provides binding sites for VEGF and thus enables the sustained release of VEGF. In vitro release test confirms the sustained releasing profile of VEGF, and stable release was observed over a time period of 25 days. In vitro cell assay indicates that VEGF release significantly promoted the proliferation of endothelial cells. More importantly, in vivo subcutaneous implantation reflects that vascularization has been effectively enhanced in the PCL/gelatin scaffolds compared with the PCL counterpart due to the sustained release of VEGF. Therefore, the heparinized PCL/gelatin scaffolds developed in this study may be a promising candidate for regeneration of complex tissues with sufficient vascularization.